The Skywalker Saga: A Bibliometric Analysis on Product Innovation in the Era of Artificial Intelligence - Mustafa, Muh. Yushar; Mustafa, Riad; Haeruddin, M. Ikhwan Maulana; Putra, Muh. Al Fatah Arief (PT Smart Media Makassar, 2025)
Product innovation is a key driver of economic growth and corporate competitiveness. Artificial intelligence (AI) is revolutionising product innovation, influencing how products are developed, marketed and used. This study aims to map the research landscape on product innovation and AI through bibliometric analysis. Data are collected from scientific publication databases such as Google Scholar, Scopus, and Web of Science, covering publications from 2000 to 2023. Bibliometric analysis is performed using VOSviewer and Publish or Perish software to identify publication trends, author collaborations, research themes, and keywords. As for theoretical contribution, the results of the study show a significant increase in related publications, strong interdisciplinary collaboration, and dominant research themes such as the use of AI in product design, AI-based market analysis, and smart product development. As for managerial contribution, this study provides insights into the challenges and opportunities associated with the use of AI for product innovation, which can help companies make more informed decisions and drive innovation in various industrial sectors.